Screening Program for Idiopathic Scoliosis by Adam's Bending Forward Test of Prepubertal Children at Primary Schools in Baghdad City - Saleh, Buthainah; Ma΄ala, Eqbal (Iraqi National Journal of Nursing Specialties, 2014)
Objective: The study aimed to screen the prepubertal children for idiopathic scoliosis at earlier stages, and findout the relationship between idiopathic scoliosis and demographic data such as age, sex, body mass index,heavy backpacks, and heart & lung diseases.Methodology: A descriptive study was conducted on screening program for prepubertal children in primaryschools at Baghdad city, starting from 24th of February to the end of October 2010. Non- probability(purposive) sample of 510 prepubertal children were chosen from primary schools of both sides of Al-Karkhand Al-Russafa sectors. Data was collected through a specially constructed questionnaire format include (24)items multiple choice questions, and researcher observation. The validity of the questionnaire was determinedthrough a panel of experts related to the field of the study, and the reliability through a pilot study. The datawere analyzed through the application of descriptive statistical analysis frequency, & percentages, andinferential statistical analysis, chi-square, are used.Results: The study results revealed that most of the prepubertal children have idiopathic scoliosis, two third ofthe sample (88.4%) were at age 10-12 years and mostly boys. There is highly significant association with (lowBody Mass Index & carry of the school backpack) but no significant association with the age, gender, and lung& heart diseases. There is highly significant association between prepubertal children's idiopathic scoliosis signs& the researcher observation for the prepubertal body feature, and Adam's Bending Forward Test whichrevealed highly significant association with their idiopathic scoliosis. The results of the study reflect that themajority of prepubertal children's idiopathic scoliosis deformities have significant association at early detectionthan the other spinal deformities (kyphosis & kyphoscoliosis).Recommendation: The researchers recommended that Ministry Of Health should activate the screening programof scoliosis within school health service programs, and Ministry of Education should be involved their teachers inthe screening & training program.